Reform des Tierschutzrechts Die Verwirklichung des Staatsziels Tierschutz de lege lata - Bülte, Jens; Felde, Barbara; Maisack, Christoph (Das Recht der Tiere und der Landwirtschaft, 2022)
How can the current animal welfare law be changed to protect animals more effectively? This work assesses and evaluates the necessary changes to the legal situation. Furthermore, the work contains a proposal for a new animal protection law with specifications for animal husbandry, animal experiments, animal transports, a penal norm and the instrument of the nationwide valid association complaint for animal protection officers and recognized animal protection organizations. Long-standing demands, e.g. for effective fire protection regulations for animal stables, bans on certain forms of husbandry and a ban on the exhibition of wild animals in circuses, are also taken up and specifications permissible under European law are formulated. With contributions by Prof. Dr. Jens Bülte; Anna-Lena Dihlmann, LL.B.; Ri'in Dr. Barbara Felde; RAin Linda Gregori and RiAG a.D. Dr. Christoph Maisack and an introduction by Renate Künast.